Neuromuscular disease‐specific questionnaire to assess quality of life in patients with chronic inflammatory demyelinating polyradiculoneuropathy. Issue 1 (14th February 2018) - Kacar, Aleksandra; Bjelica, Bogdan; Bozovic, Ivo; Peric, Stojan; Nikolic, Ana; Cobeljic, Mina; Petrovic, Milutin; Stojanov, Aleksandar; Djordjevic, Gordana; Vukojevic, Zoran; Dominovic‐Kovacevic, Aleksandra; Stojanovic, Miroslav; et al.
Abstract: To date, generic questionnaires have been used to investigate quality of life (QoL) in chronic inflammatory demyelinating polyradiculoneuropathy (CIDP) patients. Although these measures are very useful, they are not usually precise enough to measure all specific characteristics of the disease. Our aim was to investigate QoL using the neuromuscular disease‐specific questionnaire (individualized neuromuscular quality of life, INQoL) in a large cohort of patients with CIDP. Our study comprised 106 patients diagnosed with CIDP. INQoL questionnaire, Medical Research Council (MRC) sum score, Inflammatory Neuropathy Cause and Treatment (INCAT) disability score, Visual Analogue Pain Scale, Beck Depression Inventory, and Krupp's Fatigue Severity Scale were used in our study. Physical domains of INQoL were more affected than mental, and the overall score was 57 ± 25. Significant predictors of higher INQoL score in our patients with CIDP were severe fatigue (β = 0.35, p < 0.01), higher INCAT disability score at time of testing (β = 0.29, p < 0.01), and being unemployed/retired (β = 0.22, p < 0.05). QoL was reduced in our cohort of CIDP patients, which was more pronounced in physical segments. Patients with fatigue, more severe disability, and unemployed/retired need special attention of neurologists because they could be at greater risk to have worse QoL.